Variability of fish consumption within the 10 European countries participating in the European Investigation into Cancer and Nutrition (EPIC) study - Welch, AA; Lund, E; Amiano, P; Dorronsoro, M; Brustad, M; Kumle, M; Rodriguez, M; Lasheras, C; Janzon, L; Jansson, J; Luben, R; Spencer, EA; et al. (Public health nutrition, 2002)
To describe and compare the consumption of total fish (marine foods) and the fish sub-groups - white fish, fatty fish, very fatty fish, fish products and crustacea, in participants from the European Investigation into Cancer and Nutrition (EPIC) study. Cross-sectional analysis of dietary intake using a computerised standardised 24-hour recall interview. Crude means, means and standard errors adjusted by age, season and day of the week were calculated, stratified by centre and gender. Twenty-seven redefined centres in the 10 European countries participating in the EPIC study. In total, 35 955 subjects (13 031 men and 22 924 women), aged 35-74 years, selected from the main EPIC cohort. A six- to sevenfold variation in total fish consumption exists in women and men, between the lowest consumption in Germany and the highest in Spain. Overall, white fish represented 49% and 45% of the intake of total fish in women and men, respectively, with the greatest consumption in centres in Spain and Greece and the least in the German and Dutch centres. Consumption of fatty fish reflected that of total fish. However, the greatest intake of very fatty fish was in the coastal areas of northern Europe (Denmark, Sweden and Norway) and in Germany. Consumption of fish products was greater in northern than in southern Europe, with white fish products predominating in centres in France, Italy, Spain, The Netherlands and Norway. Intake of roe and roe products was low. The highest consumption of crustacea was found in the French, Spanish and Italian centres. The number of fish types consumed was greater in southern than in northern Europe. The greatest variability in consumption by day of the week was found in the countries with the lowest fish intake. Throughout Europe, substantial geographic variation exists in total fish intake, fish sub-groups and the number of types consumed. Day-to-day variability in consumption is also high.